SEBUAH TINJAUAN SISTEMATIK LITERATURE REVIEW: HUBUNGAN ATTACHMENT STYLES DALAM MENJALANI HUBUNGAN PADA INDIVIDU DEWASA - Muhtar, Shabrina; Retno Suminar, Dewi (Lafadz Jaya Publisher, 2024)
The style of attachment to the individual can be an important factor in a person's satisfaction to undergo a relationship because it can predict individual expectations of the relationship that is being lived (Marchand, 2004). Attachment itself is a human desire to establish a relationship that has mutual affection with other individuals, and determines the direction of the relationship. Individuals who undergo a relationship, both in dating and marriage, of course have a different type of attachment. This study is a literature review with a systematic approach that aims to determine the attachment style relationship that adults have in their romantic relationship. The total number of articles is 11 articles from the Google scholar database and the SAGE Journal. In this case, the hypothesis of this study is that there is a correlation between attachment style and individual satisfaction with relationships.